The Porous Characters of Flannery O'Connor and the Buffered Characters of Walker Percy. - SYKES, JOHN D. (Logos: A Journal of Catholic Thought & Culture)
The article distinguishes Flannery O'Connor and Walker Percy through Charles Taylor's concepts of the porous self and the buffered self, showing how O'Connor's characters remain open to divine grace while Percy's reflect the closed, secularized modern consciousness. Topics include the porous self's openness to supernatural influence, the buffered self's insulation by optionality and scientism; and the use of violence and dialogue as contrasting narrative strategies.